Surgical Reconstruction in Chronic Posterior Cruciate Ligament Injuries of the Knee - A, Che Ahmad; NMF, Najmi; OC, Samsudin; JK, Yeap; MY, Hyzan (IIUM Medical Journal Malaysia, 2015)
Introduction: This is a cross-sectional study to evaluate the outcome of posterior cruciate ligament reconstruction in chronic injuries using ipsilateral Bone-patella tendon-Bone graft in nine patients, between January 2000 and January 2003 at our institution. Methods: Eight male and one female patient; their ages ranged from 18 to 36 years old. The surgery was done at an average of 17.2 months (range from 3 and 40 months) post injury. All patients were followed up for a minimum of two years period. The assessment was done at twelve and twenty-four months using Lysholm knee score, IKDC knee examination evaluation score and arthrometric measurement with KT-2000. Results: The result showed only moderate success in restoration of ligament stability with 73.4% satisfactory objective results. However, the functional improvement and patient satisfaction is only 55%. The incidences of degenerative changes were 89% at the time of operation. Conclusion: Surgical reconstruction of chronic Posterior Cruciate Ligament restored satisfactory stability of the knee but the functional outcome was only moderate.